Ongoing egocentric spatial processing during learning of non-spatial information results in temporal-parietal activity during retrieval - Gomez, Alice; Cerles, Mélanie; Rousset, Stéphane; Lebas, Jean-françois; Baciu, Monica (Frontiers in Psychology, 2013)
Deficits in amnesic patients suggest that spatial cognition and episodic memory are intimately related. Among the different types of spatial processing, the allocentric, relying on the hippocampal formation and the egocentric-updated, relying on parieto-temporal connections have both been considered to functionally underlie episodic memory encoding and retrieval. We explore the cerebral correlates underlying the episodic retrieval of words previously learnt outside the magnet while performing different spatial processes, allocentric and egocentric-updated. Subsequently and during fMRI, participants performed an episodic word recognition task. Data processing revealed that the correct recognition of words learnt in egocentric-updated condition enhanced activity of the medial and lateral parietal, as well as temporal cortices. No additional regions were activated in the present study by retrieving words learnt in allocentric condition. This study sheds new light on the functional links between episodic memory and spatial processing: The temporo-parietal network is confirmed to be crucial in episodic memory in healthy participants and could be linked to the egocentric-updated process.